Predictors of Weight Gain and Metabolic Indexes among Men Admitted to Forensic Psychiatric Hospital. Issue 2 (3rd April 2022) - Hilton, N. Zoe; Ham, Elke; Hill, Stephanie; Emmanuel, Talia; Konkolÿ Thege, Barna
Abstract: People with mental health disorders face elevated risk of metabolic syndrome (MetS), which increases the risk of serious health problems and premature mortality. Obesity is prevalent among those hospitalized in forensic psychiatric units, and substantial weight gains during hospitalization have been reported. We examined International Diabetes Federation (IDF) criteria and proxy MetS indexes (body mass index [BMI], blood pressure, and waist circumference) in the medical records of 527 men admitted to a forensic hospital, and tested predictors of weight gain during their first year or less in hospital. IDF indexes were documented for 22% of men whereas proxy indexes were documented for 46%. Both suggested similar MetS prevalence: 16% IDF, 17% proxy. Weight gain averaged 1.72 kg per month; BMI, being a smoker, and length of stay were independent predictors. Interventions focusing on these risk factors are advisable in order to support both mental and physical health among individuals admitted to forensic psychiatric services. The proxy MetS indexes offer a rapid screening measure and a promising tool for research studies and clinical practice in the absence of blood test results.